That Further Shore : A Memoir of Irish Roots and American Promise - Feerick, John D.; Shelley, Thomas J. (New York, NY : Fordham University Press, 2020)
A rare and evocative memoir of a respected constitutional scholar, dedicated public servant, political reformer, and facilitator of peace in the land of his ancestors.John D. Feerick’s life has all the elements of a modern Horatio Alger story: the poor boy who achieves success by dint of his hard work. But Feerick brought other elements to that classic American success story: his deep religious faith, his integrity, and his paramount concern for social justice. In his memoir, That Further Shore, Feerick shares his inspiring story, from his humble beginnings: born to immigrant parents in the South Bronx, going on to practice law, participating in framing the U.S. Constitution’s Twenty-Fifth Amendment, serving as dean of Fordham Law, and serving as President of the New York City Bar Association and chair of state commissions on government integrity.Beginning with Feerick’s ancestry and early life experiences, including a detailed genealogical description of Feerick’s Irish ancestors in County Mayo and his laborious quest to identify them and their relationships with one another, the book then presents an evocative survey of the now-vanished world of a working-class Irish Catholic neighborhood in the South Bronx. Feerick’s account of how he financed his education from elementary school through law school is a moving tribute to the immigrant work ethic that he inherited from his parents and shared with many young Americans of his generation. The book then traces Feerick’s career as a lawyer and how he gave up a lucrative partnership in a prestigious New York City law firm at an early age to accept the office of Dean of the Fordham School of Law at a fraction of his previous income because he felt it was time to give back something to the world.John Feerick has consistently shown his commitment to the law as a vocation as well as a profession by his efforts to protect the rights of the poor, to enable minorities to achieve their rightful places in American
That Further Shore -- Frontmatter -- Contents -- Foreword -- Preface -- Introduction -- Part I: My Family and Its Irish History -- 1. What’s in a Name? -- 2. Mom’s and Pop’s Origins -- 3. Mom’s and Pop’s Childhood -- Part II: A New Home in America -- 4. An American Odyssey -- 5. Settling in the Bronx -- 6. Growing Up in an Irish Immigrant Family -- 7. Uncle Pat, Our Life- Long Companion -- 8. Memories of the Nearby House That Ruth Built -- Part III: My Salad Days -- 9. St. Angela Merici Grammar School, 1942–1950 -- 10. Bishop Dubois High School, 1950–1954 -- 11. Fordham College, 1954–1958 -- 12. Fordham Law School, 1958–1961 -- 13. Meeting the Love of My Life: Emalie -- Part IV: Career as a Lawyer -- 14. Learning in Part- Time Jobs -- 15. Joining a Small Law Firm—Skadden, Arps, Slate, Meagher & Flom -- 16. Leaving Skadden -- 17. Becoming a Law School Dean: An Overview -- 18. Commitments, Challenges, and Special Moments -- 19. The Many Hats a Dean Wears -- 20. Fordham Law Goes to Ireland -- 21. Leaving the Deanship -- 22. Becoming a Classroom Teacher -- Part V: The Vocation of Service -- 23. Serving Others -- 24. The Voluntary Bar -- 25. Public Service: From Carey to Koch to Cuomo to Bloomberg to Kaye -- 26. Boards of Not- for- Profit, Charitable, and Public Institutions -- 27. The Catholic Church -- Part VI: Peacemaking and Problem- Solving -- 28. Learning the Art of Conflict Resolution -- 29. Conflicts in the Public Eye -- Part VII: Constitutional Endeavors -- 30. Presidential Succession -- 31. The Electoral College System -- 32. Other Constitutional Opportunities -- Part VIII: The World of Government Ethics -- 33. The New York State Commission on Government Integrity -- 34. New York State Ethics Commission -- 35. The New York State Public Integrity Commission -- Part IX: Marriage and Family --
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 28. Sep 2020)
Keywords: Bronx; Fordham University; immigrant stories; New York State Ethics Commissions; Presidential Inability; Skadden Arps; sport arbitrations; the Electoral College System; BIOGRAPHY & AUTOBIOGRAPHY / Lawyers & Judges